(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2018)
During 1950s in Italy wild boar (Sus scrofa) was close to extinction. Then, several introduction, re-introduction and restocking operations have been legally carried out by local administrations, or illegally by hunters for hunting purpose, so as to make the management of this species particularly problematic and needing a careful and farsighted approach. In order to limit the increasing damage to crops and biocenosis, containment plans have been carried out, even in hunting-free areas, through selective cull and capture with steady or movable cage. The destination of captured animals is the critical point of this kind of management, not only for the effectiveness of this practice but above all for animal welfare. Often these animals are destinated to game farms, private hunting areas or hunting dogs training areas. Moreover, transport of live wild boars to slaughterhouses does not respect animal welfare standards and is in contrast with European legislation for animal welfare during transport and animal management in slaughterhouse. Considering the current practices, the authors outline the current legislative framework on the subject and propose indications to include the activities of wild boar containment within the commercial chain of wild game meat. Moreover, the transport of alive wild boars to slaughterhouses is in contrast with European Regulation admitting this transport only for listed farmed animals. Considering the above-mentioned practices, the Authors outline the current legislative framework on the subject, and in the context of the activities of containment of wild boars, ask for an immediate suppression of the animals directly on the capture location, avoiding any subsequent handling and transport.